A belief-based bitemporal database model - Jiratanachit, Wajee; Chittayasothorn, Suphamit (My University, 2015)
Current bitemporal data models use valid time and transaction time to indicate the time that a fact is valid in a domain, and the time that the fact is stored in a database respectively. In order to store historical data with different beliefs during the same valid time period, there need to be a time dimension which indicates the belief time; the time that the fact is believed to be true. This belief time is different from the conventional transaction time, which is the time that the fact is entered into the database. In this paper, a belief-based approach to bitemporal data model is presented together with its query and manipulation considerations.
Keywords: Belief time; Bitemporal; Temporal database; Transaction time; Valid time